PENGARUH PERENDAMAN DALAM CAMPURAN LARUTAN GARAM DAN EKSTRAK DAUN JAMBU BIJI TERHADAP KANDUNGAN LEMAK DAN PROTEIN TELUR AYAM RAS - Eerstanthy Novelita; N. Nuruz Zaman (Jurnal Ilmiah Fillia Cendekia, 2017)
The aim of this research was to find influence soaking in a mixture of salt solutions and guava leaf extract against a fat and protein contain of egg. This study was conducted in the laboratory of animal husbandry, Faculty of Agriculture, Kadiri Islamic University on 20 -26 june 2014 and eggs sample were analyzed the fat and the protein contain in the laboratory of biochemistry, MIPA Faculty, UMM on 27-30 june 2014. Methodology of this research used was the factorials method Completed Random Design (RAL). Research factors includes: immersion in a solution of salt, consisting of 2 level: T0: without additional salt; T1: by the addition of 15 %salt and factors soaking in guava leaf extract, consists of 4 level: D0: without additional guava leaf extract; D1: by the addition of 10% guava leaf extract, D2: by the addition of 20% guava leaf extract; d3: by the addition of 30% guava leaf extract.The total number of eggs required in this study was 96 egg with weights between 50-60 grams The results of the analysis showed that treatment of soaking in a mixture of salt solutions and guava leaf extract produce a fat and protein content of eggs with no significant different (P>0.05). The average of fat content (%) in each combination treatment: T0D0= 12,618 ± 0,345 ; T0D1= 12,012 ± 0,194 ; T0D2= 12,054 ± 0,323 ; T0D3= 11,208 ± 0,227 ; T1D0 = 12,391 ± 0,280 ; T1D1= 11,780 ± 0,249 ; T1D2= 11,458 ± 0,144 ; T1D3= 10,737 ± 0,321. The average of protein content (%) in each combination treatment: T0D0= 14,684 ± 0,087 ; T0D1= 14,913 ± 0,127 ; T0D2= 14,912 ± 0,047 ; T0D3= 15,003 ± 0,055 ; T1D0= 14,769 ± 0,088 ; T1D1= 14,997 ± 0,056 ; T1D2= 14,975 ± 0,058 ; T1D3= 15,062 ± 0,047. The conclusions of this research was not significantly different (P>0,05) use a mixture of salt solutions and dosage guava leaf extractin soaking egg against a fat and protein content.Suggested should be used combination treatment immersion in a solution of salt and 30% guava leaf extract to maintain a fat content and protein of egg and further investigation to determine the level of consumer test (organoleptic) of egg who received treatment in a solution of salt and guava leaf extract.